Application of Project Based Learning Models in Improving Creative Thinking of Students at Physics Lessons in SMA Bandar Baru - Muchsin Muchsin; Mariati Mariati (Budapest International Research and Critics University, 2020)
The ability to think creatively is necessary given that today science and technology are developing very rapidly and allows anyone to be able to obtain information quickly and easily with abundance from various sources and anywhere in the world. This has resulted in rapid changes in the order of life as well as global changes in life based on developments in the era of the industrial revolution 4.0 where communication skills and skills are the main focus. If they are not equipped with the ability to think creatively, they will not be able to process assess and retrieve the information needed to face these challenges. This study uses quantitative research methods aimed at improving the creative thinking of physics students by using the Project Based Learning learning model. The types of instruments used in this study include Observation Sheets, LKPD sheets which are oriented towards the 2013 curriculum, creative thinking test instruments and learning implementation instruments. The results of this study can be concluded that there was an increase in the ability to think creatively after the Project Based Learning model was applied. The average n-gain acquisition in experimental class I was 0.75 and classified in the high category and in experimental class II was 0.77 and classified in high category, with an average acquisition of n-gain values of both classes of 0.76 with a high category.